2021
DOI: 10.1108/prt-08-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Damage caused by black inks to the chemical properties of archaeological papyrus – analytical study

Abstract: Purpose The purpose of this study is to determine the nature of archaeological papyrus damage and monitoring the mechanics of damage caused by black inks to the chemical properties of ancient papyrus. Design/methodology/approach This study the papyrus surface with a digital microscopy “USB,” examination and analyzing by “Scanning Electron Microscope,” characterization of black ink used in writing the ancient papyrus using “Scanning Electron Microscopy” with (EDX). Detection of changes in the chemical bonds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…An increase in the O–H hydroxyl group represented by the band at 3420 cm −1 was observed, indicating hydrolysis of cellulose fibers due to infection of the papyrus samples and secretion of cellulase enzyme and acid by fungi, as confirmed in the first section. A similar result was observed by Mazen et al (2021), who monitored the hydrolysis of archaeological papyrus after exposure to high water content by a slight increase in the band at 3424 cm −1 . Carbonyl groups (–CO, –COOH, and –CHO) occur on the broken ends of macromolecular chains in the spectra of cellulosic materials, as papyrus is considered a good candidate for monitoring the changes caused by oxidation and therefore cellulose degradation (Abdel‐Maksoud & El‐Amin, 2013; Łojewska et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…An increase in the O–H hydroxyl group represented by the band at 3420 cm −1 was observed, indicating hydrolysis of cellulose fibers due to infection of the papyrus samples and secretion of cellulase enzyme and acid by fungi, as confirmed in the first section. A similar result was observed by Mazen et al (2021), who monitored the hydrolysis of archaeological papyrus after exposure to high water content by a slight increase in the band at 3424 cm −1 . Carbonyl groups (–CO, –COOH, and –CHO) occur on the broken ends of macromolecular chains in the spectra of cellulosic materials, as papyrus is considered a good candidate for monitoring the changes caused by oxidation and therefore cellulose degradation (Abdel‐Maksoud & El‐Amin, 2013; Łojewska et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…We can observe a dramatic increase in C–H bending vibration at 796 cm −1 ; furthermore, the C–H stretching, C–H bending, C-O-C pyranose ring vibration and glycosidic linkage between glucose units in cellulose, respectively, appeared stronger after cleaning with 1% of alkyl dimethylbenzyl ammonium chloride; besides that, organic carbon, quartz and kaolinite vibrations totally disappeared. This confirms with tangible evidence the support of the cellulose construction by this new cleaner in addition to its ability to remove dust and dirt (Mary et al , 1989). On other hand, this carbonyl band was shifted to be smaller which confirmed that the initial pH increases.…”
Section: Resultssupporting
confidence: 81%
“…We can detect topical variations of paper sample (Figure 5) but with observable decrees in their intensities such as C=O stretching vibration at 1,029 cm-1 and C-H bending vibration at 768 cm -1 ; furthermore, we can observe notable shift in C-H bending vibration where it was shifted at 768 cm À1 added to the totally disappeared C-H stretching because of aromatic and symmetric stretching (Hassan, 2015(Hassan, , 2021Michele, 1999), which can be attributed to the effect of oxidation mechanism for the historical paper especially; there is a notable increase of spectra in the various carbonyl groups (products of paper aging) at 1,559 and 1,637 cm À1 . Besides these results the illite, kaolinite, montmorillonite, imogolite vibrations at 660, 1,029 and 3,389 cm À1 (Clay minerals) were observed in samples which confirmed a present of dust particles on the historical paper structure furthermore the FTIR detected vibrations of organic carbon and quartz at 2,876 and 768 cm À1 , respectively.…”
Section: Historical Sample Before Cleaningmentioning
confidence: 90%
See 1 more Smart Citation
“…Organic objects are rapidly affected by a combination of deterioration agents, resulting of environmental factors or chemical factors. Generally, papyrus the most important writing material was manufactured from Cyperus papyrus L strips which would be laid down in two layers, one vertical and one horizontal in a grid pattern, pressed and dried to obtain papyrus sheets (Bataa et al , 2021).…”
Section: Introductionmentioning
confidence: 99%